Corporate Vulnerabilities in India and Banks' Loan Performance - Lindner, Peter (IMF Working Papers; Working Paper ;, 2014)
The financial performance of India's corporate sector has been under pressure since the Global Financial Crisis. Balance-sheet data on a large cross-section of Indian non-financial corporates show that the growth in their leverage over the last 15 years has been associated with a notable increase in the vulnerabilities of firms carrying high interest payment burdens. Gauged by the debt carried by the most vulnerable component of firms, the Indian corporate sector's vulnerability to severe systemic shocks has increased to levels not seen since 2001. Progress on the macroeconomic front, together with improved credit appraisals and stricter impairment standards on the bank side, will be critical to help India's banks resume their role as economic growth drivers.